Filantropi Pembiayaan Lembaga Pendidikan Anak Usia Dini - Hidayat, Imam; Utami, Rahmi Bekti; Samiaji, Mukhamad Hamid (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
This research on Philanthropy for The Financing of Educational Institutions in KB Al Hikmah Purworejo was conducted to find out about how philanthropy financing is carried out in kb AL Hikmah Purworejo. The method used in this article is a type of qualitative descriptive research. Data collection techniques are carried out with observations, interviews and documentation. The analysis techniques carried out are the presentation of data, and draw conclusions. The results of this study show that philanthropy financing is still needed in kb Al Hikmah institutions considering the needs of institutions that have not been able to be fully independent. With the philanthropy by the community also supports learning activities so that kb Al Hikmah institutions remained until now even in pandemic situations. Philanthropic activities financing by the community there are carried out routinely every month such as the addition of teacher salaries, payment of electricity and water accounts. So with the philanthropy financing of this institution is very helpful in the process of learning and improving the quality of early childhood education